Implementasi Strategi Pemasaran Untuk Meningkatkan Omset Penjualan Toko Kelontong (Studi Kasus: Toko Kelontong Nue Cell) - Danis Supriadi; Deri Apriadi (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
Grocery stores are a common type of business found in various areas, especially in residential neighborhoods. One of the main challenges faced by grocery stores is increasing sales revenue amid intense market competition. This article discusses the marketing strategies implemented by Nue Cell Grocery Store to boost their sales revenue. Through interviews with the store's owner and manager, it was found that the marketing strategies focus on competitive pricing, excellent customer service, and effective promotions. The research results indicate that the implementation of these strategies has successfully increased sales revenue and significantly attracted new customers. The store’s approach of offering lower prices than competitors, coupled with good service and word-of-mouth promotion, has proven effective in building customer loyalty and generating higher sales volumes. This case study demonstrates how even small grocery stores can thrive by adopting customer-centered marketing practices that emphasize value, service, and community engagement.